Pengaruh CAR, NPF, FDR Terhadap Profitabilitas di Bank BTPN Syariah Tahun 2014-2024 - Andriani, Fira Juni; Ardiani, Ninda (Al - Muamalat: Jurnal Hukum dan Ekonomi Syariah, 2025)
This study aims to analyze the effect of Capital Adequacy Ratio (CAR), Non-Performing Financing (NPF), and Financing to Deposit Ratio (FDR) on the profitability of Bank BTPN Syariah during the 2014–2024 period. The main focus of this research is how these three variables influence Return on Assets (ROA) as an indicator of bank profitability. The research employs a quantitative method with a multiple linear regression analysis approach. The data analyzed is secondary data obtained from the quarterly financial statements of Bank BTPN Syariah over the 2014–2024 period. The dependent variable in this study is ROA, while the independent variables include CAR, NPF, and FDR. Data analysis is conducted using SPSS and Microsoft Excel software. The results show that CAR has a positive and significant effect on ROA, whereas NPF has a negative and significant effect on ROA. Meanwhile, FDR does not have a significant impact on ROA. Simultaneously, CAR, NPF, and FDR significantly affect the profitability of Bank BTPN Syariah. This study contributes by strengthening empirical evidence regarding the effect of CAR, NPF, and FDR on the profitability of Islamic banks, particularly in Indonesia.